challenges hindering energy provision - Kioko, Jane (Kabarak university, 2012)
Among the challenges hindering energy provision is the loss of revenue as a result of poorly managed revenue collection systems. This study examined the effect of prepaid meters on revenue collection, a case of Kenya power, Nakuru, Kenya. The study used a survey research design to establish effects of prepaid meters on revenue collection efficiency. 396 prepaid meters in Nakuru County were targeted. A sample of 201 respondents was selected using Stratified random sampling technique. The study used primary data captured by use of questionnaires. Data was analysed using both Descriptive and Inferential Statistics with the aid of Statistical Package for Social Sciences (SPSS) version 20. Descriptive Statistics used included mode, percentages and frequencies. For inferential statistics, Pearson Correlation and Multiple Regression were used. The findings were presented in form of tables. Study findings indicated that perceived risk was negatively correlated to revenue collection (β1=-.182, ρ<0.05), while perceived ease of use (β2= 0.342, ρ<0.05), perceived low cost (β3=.823, ρ=<0.05) and perceived usefulness (β4= 0.131, ρ<0.05) were positively related and had a significant effect on revenue collection. This study therefore, affirms that perceived risk reduces revenue collection, while perceived ease of use, perceived low cost and perceived usefulness enhance revenue collection. The Kenya Power company should enhance security of customers so that they do not suffer losses. Customer care service should increase their service delivery to customers so that users can have required knowledge on the use of prepaid meters. The use of prepaid meters should be improved since they improve management of daily power consumption of customers, advance the revenue collection process, save time and regulation of electricity consumption. Key
Keywords: CHALLENGES HINDERING ENERGY PROVISION